Perancangan Robot Pemadam Api Divisi Senior Berkaki - Helman Muhammad, Latif Hidayat Iswanto (Universitas Muhammadiyah Yogyakarta, 2011)
The main objective of this study is to use a good method to control the robot that capable of detecting the presence of light and avoiding obstacles in front of the robot without hitting the obstacles that may obstruct it. Legged robot uses sensors to detect the presence of photodioda the firelight and ultrasonic sensors (PINGTM) is to detect the presence or absence of obstacles so that legged robots are able to walk without bumping into obstacles that may obstruct it. A servo motor was used for driving the wheel of the feet. In this research, legged robots have been able to go scour the walls and extinguish the fire.